2020
DOI: 10.30835/2413-7510.2020.222348
|View full text |Cite
|
Sign up to set email alerts
|

Genetic resources of chickpea and the efficiency of their use in breeding

Abstract: Січкар В.І. Одеська державна сільськогосподарська дослідна станція НААН України У статті узагальнено характеристику цінних господарських ознак колекційних зразків нуту за посушливих умов Степу України. Наведено дані з розповсюдження культури на нашій планеті, показано позитивний вплив на здоров"я людей виготовлених із його насіння продуктів харчування. Виділено та описано низку генотипів, які поєднують значну кількість важливих агрономічних ознак та мають значну цінність для селекції. Особливу увагу в дослідже… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…SCV is used when characterizing individual combinations if they are better or worse than expected based on the average values of the studied varieties [8]. It was found that there is a positive correlation between the amount of heterosis in the first generation, the degree and frequency of transgressions in weight (r = 0.75, r = 0.31) and the number of beans per plant (r = 0.35, r = 0.23), as well as the number of beans on the main stem (r = 0.65, r = 0.42) [14].…”
mentioning
confidence: 99%
“…SCV is used when characterizing individual combinations if they are better or worse than expected based on the average values of the studied varieties [8]. It was found that there is a positive correlation between the amount of heterosis in the first generation, the degree and frequency of transgressions in weight (r = 0.75, r = 0.31) and the number of beans per plant (r = 0.35, r = 0.23), as well as the number of beans on the main stem (r = 0.65, r = 0.42) [14].…”
mentioning
confidence: 99%
“…According to the results of studies by Sichkar V.I. [4,5], Biliavska L. et al [6], the negative weather trend (increased air temperature, long inter-rain periods, frequent dry spells and heavy rains), which has intensified in recent years, requires the creation of fundamentally new varieties, the main characteristic of which is increased adaptability, which is expressed in the stability of the yield over the years. We believe that this is the main feature of modern plant breeding.…”
mentioning
confidence: 99%
“…Only determining the productivity of plants over a long period of time under different conditions makes it possible to objectively assess the genotype in terms of adaptability. At present, the amount of precipitation in most of our country is the main limiting factor of yield [4,5].…”
mentioning
confidence: 99%
See 2 more Smart Citations